The molecular tumor board as a step in cancer patient management: a southern Italian experience - Tommasi, Stefania; Maurmo, Leonarda; Rizzo, Alessandro; Carella, Claudia; Ranieri, Girolamo; De Summa, Simona; Mannavola, Francesco; Chiurì, Vincenzo Emanuele; Guida, Michele; Nisi, Claudia; Montrone, Michele; Giotta, Francesco; et al. (Frontiers in Medicine, 2024)
The management of cancer patients follows a Diagnostic Therapeutic and Care Pathway (PDTA) approach finalized at the best balance between care and quality of life. To support this process, precision medicine and innovative technologies (e.g, next-generation sequencing) allow rapid identification of genetic-molecular alterations useful for the design of PDTA-approved therapies. If the standard approach proves inadequate, the Molecular Tumour Board (MTB), a group comprising specialists from diverse disciplines, can step in to evaluate a broader molecular profile, proposing potential therapies beyond evidence levels I-II or considering enrolment in clinical trials. Our aim is to analyze the role of the MTB in the entire management of patients in our institute and its impact on the strategy of personalized medicine particularly when all approved treatments have failed.Material and Methods: Accordingly with European and national guidelines, a panel of clinicians and preclinical specialists from our Institution was defined as the MTB core team and a procedure for the operation of this multidisciplinary group, the only one operating in the Puglia region, has been designed and approved.In 29 months (2021-2023) we discussed and analyzed 93 patients. 44% presented pathogenic alterations, of which 40.4% were potentially actionable. Only 11 patients were proposed to be enrolled in clinical trials or treated with off-label drugs or Italian Pharmaceutical Agency for Drugs (AIFA) 5% funding. Our process indicators, time to analysis and number of patient cases discussed are in line with the median data of other European institutions. Such findings underscore both the importance and the usefulness of the integration of a MTB process into the care of oncology patients.